PENGEMBANGAN BAHAN AJAR BERBASIS MICROLEARNING MELALUI PLATFORM WHATSAPP UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA - Daniati, Maretza Dwi; Mutaqin, Anwar; Ihsanudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and test the feasibility and effectiveness of microlearning-based teaching materials integrated through the WhatsApp platform in improving students' understanding of mathematical concepts in trigonometry. The study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects were 10th grade students at SMA Negeri 7 Kota Serang. The research instruments included expert validation sheets, student response questionnaires, and concept comprehension tests in the form of pre-tests and post-tests. The results showed that the teaching materials developed were very feasible based on expert validation. Student responses indicated that the teaching materials were practical to use. The effectiveness test results showed an increase in students' mathematical concept comprehension, as indicated by an increase in posttest scores and an N-Gain score of 0.66 in the moderate category. Thus, microlearning teaching materials via WhatsApp are effective as a medium for mathematics learning.